Treatment with pentosan polysulphate in patients with MPS I: results from an open label, randomized, monocentric phase II study. Issue 6 (2nd September 2016) - Hennermann, Julia B.; Gökce, Seyfullah; Solyom, Alexander; Mengel, Eugen; Schuchman, Edward H.; Simonaro, Calogera M.
Abstract: Current treatment options for MPS I have limited effects on some organs, including the skeletal system. In MPS animal models pentosan polysulphate (PPS) reduces the concentrations of glycosaminoglycans (GAGs) in tissues and body fluids and improves cartilaginous and osseous pathologies. The goals of this study were to investigate primarily the safety and secondary the clinical effects, concerning mobility and pain, of PPS treatment in MPS I patients. Four MPS I‐Hurler‐Scheie/‐Scheie patients aged 35.6 ± 6.4 years with one male were included in the study. All patients were on enzyme replacement therapy since 9.45 ± 3.75 years. PPS was applied subcutaneously in two patients with 1 mg/kg and in two patients with 2 mg/kg, weekly for 12 weeks and then biweekly for 12 weeks. The 24‐week treatment with PPS was well tolerated by all patients. Urinary GAG concentrations were reduced from 4.13 ± 1.17 at baseline to 2.69 ± 0.36 mg/mmol creatinine after 24‐week treatment with 1 mg/kg PPS, and from 6.71 ± 0.62 to 2.65 ± 0.09 mg/mmol creatinine with 2 mg/kg PPS. An improvement in range of motion was noted in three out of four patients. The pain intensity score was reduced from 4.5 ± 1.77 at baseline to 1.8 ± 0.47 after 24‐week treatment with 1 mg/kg PPS; patients with 2 mg/kg PPS already had minimal pain at the start of the study. In conclusion, PPS treatment in a small number of adult MPS I patients was well tolerated and resulted in a significant reduction of urinary GAG excretion and in an improvement of joint mobility and pain.